The Effectiveness of Mirror Therapy in Stroke Patients: A Systematic Review - Zahrotul Jannah; Yurike Septianingrum; Raden Khairiyatul Afiyah; Imamatul Faizah (Journal Of Nursing Practice, 2023)
Backgrounds : Stroke is a global problem and the second cause of death in the world. Purpose : To find out the effectiveness of giving mirror therapy in stroke patients. Methods : There are five databases used, namely Science Direct, SAGE Journal, Emerald, ProQuest and PubMed to search for mirror therapy and post-strokes. The inclusion criteria used are for publications for the last 5 years from 2017 to 2022, full-text articles and in English, according to the title, and RCT research or experimental studies. Results : of the total 7 articles submitted for this systematic review after quality assessment, this included 3 randomized controlled trials and 4 experimental studies. All muscle strength studies in post-stroke patients after being given mirror interventions experienced an increase in muscles in parts of the body that experienced hemiperation, thereby increasing independence in patients. From the results of all studies, it was found that the optimal time in starting the therapy is in the chronic stage, and the therapeutic dose is given with the same intensity (at least five sessions per week) and duration (at least 30 minutes to 90 minutes). Conclusion : mirror therapy proved to be an effective and viable approach to rehabilitate post-stroke survivors in acute, sub-acute, and chronic phases of the stroke, despite the long-term effects.